Gambaran Penggunaan Media E-Learning pada Mahasiswa S1 Keperawatan Universitas Muhammadiyah Lamongan - Yogi Galih Permadi; Suratmi Suratmi; M. Bakri Priyodwi Atmaji (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
E-Learning media is an innovation that has made a huge contribution to changes in the learning process, the contribution in question is the role of E-Learning as a supplement, complement and substitute in learning activities. This research aims to determine the use and utilization of E-learning at UMLA. This research is a quantitative descriptive study with a cross sectional design. The research sample consisted of 220 UMLA students in semesters 2, 4 and 6, taken using the random sampling method. This research was tested with a questionnaire on the use of E-learning media which was validated with SPSS. Overall, the results showed satisfaction with students' perceptions of E-learning with a total score of 78.2%. The mean value of the satisfaction level component shows good results on student perceptions of the use of E-learning. The use of E-learning media by students is categorized as satisfied. Thus, it can be concluded that the use of E-learning as a learning medium is categorized as satisfactory, which can be seen from the research results with 5 indicators in the satisfied category.